Nanostructures: Properties, Production Methods and Applications - Dong, Yu (Nova Science Publishers, Inc., 2013)
The exploration of attractive nanoscience and nanotechnology offers tremendous opportunities to implement nanostructures/nanomaterials such as nanoclays (1-D platelets), carbon nanotubes (2-D tubes) and porous nanosilicas (3-D spheres). The well-tailored nanostructures of a material play a leading role in the development of excellent mechanical, thermal, barrier, optical, structural and heat retardant properties, as well as widespread novel applications in energy storage, cosmetics, sensing devices, nanofiltration, drug delivery and semiconductors. This book presents the focus of nanostructures from three key aspects of multi-functional properties, recent production methods and real applications in multi-disciplinary fields of chemistry, material science and engineering, physics and biotechnology.